Narrator’s presence in the Algerian novel – The novels of Bachir Mefti as a model - Khadija Mehoubi, Khadija Mehoubi; El Ouakal, Zerarkal (El Omda in Linguistics and Discourse Analysis, 2024)
This research paper sheds light on the narrator in the Algerian novel, taking the novels of Bashir Mufti as a model for the study. This is due to the importance of the narrator in the work of fiction. There is no narrative without a narrator, as he is the link between the author and the reader, so he must be aware of the events taking place in order to Present it to the recipient in an appropriate manner. The aim of this study is to know the aspects of the narrator’s presence in the Algerian novel through Bashir Mufti’s novels, which show us that his presence was distinct and diverse, differing from one novel to another. ا